(untitled) (Research, Society and Development, 2021)
Dermatophytoses are superficial fungal infections that affect domestic carnivores. Microsporum and Trichophyton. are the two main genders that cause this infection with Microsporum canis, Microsporum gypseum and Tricophyton mentagrophytes, and most frequent species is M.canis. It is an anthropozoonosis of great importance in public health. The objective of this study was to evaluate the number of dermatophytoses attended in the dermatology service at HOVET-UFRA. Positivity was found in 11.98% (49/409) of the animals. 39 was canines and 10 felines. mixed breed, in both dogs and cats, were the majority in positive cases. Of these 23/39 (58.97%) were dogs and 6 (60%) were cats. There was no sexual preference among the positive animals.